2017
DOI: 10.1049/iet-nbt.2016.0148
|View full text |Cite
|
Sign up to set email alerts
|

Foley catheters functionalised with a synergistic combination of antibiotics and silver nanoparticles resist biofilm formation

Abstract: Foley catheters are inevitable in health care unit. Pathogens colonise and form biofilm on catheter causing catheter-associated urinary tract infection. Therefore, the authors aimed to functionalise catheter to resist biofilm formation. The authors impregnated urinary catheters with a synergistic combination of antibiotics and silver nanoparticles (SNPs) to evaluate antibiofilm efficacy and. SNPs were synthesised using . Synergy between the SNPs and antibiotics was determined by the checker-board method. effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Even if silver (a half-noble metal) is susceptible to quick oxidation processes, the impressive surface-to-volume atomic ratio related to AgNPs accounts for the sustained local supply of Ag + ions at the coating/tissue interface [ 129 ]. In recent studies, the role of AgNP-modified catheters as non-toxic devices capable of sustained release of bactericidal silver, exhibiting preventive effects against infection-related complications, was presented [ 116 , 130 , 131 ]. Given the fact that one of the major groups of organisms that causes device-related infections is represented by coagulase-negative staphylococci (CoNS), the effects exhibited by AgNPs and AgNP-coated catheters against these organisms were intimately studied [ 38 ].…”
Section: Silver Nanoparticles For Catheter Modificationmentioning
confidence: 99%
“…Even if silver (a half-noble metal) is susceptible to quick oxidation processes, the impressive surface-to-volume atomic ratio related to AgNPs accounts for the sustained local supply of Ag + ions at the coating/tissue interface [ 129 ]. In recent studies, the role of AgNP-modified catheters as non-toxic devices capable of sustained release of bactericidal silver, exhibiting preventive effects against infection-related complications, was presented [ 116 , 130 , 131 ]. Given the fact that one of the major groups of organisms that causes device-related infections is represented by coagulase-negative staphylococci (CoNS), the effects exhibited by AgNPs and AgNP-coated catheters against these organisms were intimately studied [ 38 ].…”
Section: Silver Nanoparticles For Catheter Modificationmentioning
confidence: 99%
“…In 2016, Rajendran and et al, impregnated urinary catheters with antibiotics (amikacin and nitrofurantoin) and a synergistic combination of antibiotics and AgNPs (synthesized by a biological method) in order to evaluate antibiofilm activity. The authors reported that the synergistic combination showed a 90% inhibition of bacterial adhesion, whereas functionalization with antibiotics showed only 25% inhibition [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silver ions are the most popular clinically tested and available coating for urinary catheters yet the effectiveness of them is still debatable due to vast differences in outcomes in vitro, in animal models and in clinical trials studies [34,51,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. The mechanisms by which silver is toxic to bacteria include disruption of the membrane, proteins, and by inducing oxidative stress through the release of silver ions into the bladder [15].…”
Section: Silver Ionsmentioning
confidence: 99%
“…Combinatorial therapies have shown positive results in vitro, examples of these combinations are: (1) silver with several antimicrobial or antifouling compounds such as norfloxacin [151], amikacin [82], nitrofurantoin [82], chlorhexidine [152]; phosphorylcholines [75]; hydroxyapatite [76]; or even plasma [153]; (2) polyzwitterions with cellobiose dehydrogenase [45]; (3) antimicrobial peptide temporin 1Tb with EDTA [154]; (4) chlorhexidine with gentian violet against Candida spp. [107], and (5) bacteriophage with a pre-established biofilm of non-pathogenic E. coli HU2117 on catheter against P. aeruginosa [155].…”
Section: Combination Therapiesmentioning
confidence: 99%